Country personality scale: is a five-dimensional model a better methodological instrument? - Búrcio, C. M. S.; Vinhas da Silva, R.; Salgueiro, M. F. (Tourism Analysis, 2016)
In this article, we investigate the Country Personality Scale and explore the use of a five-dimensional scale instead of the originally proposed six-dimensional scale and its application for evaluating consumers' behavioral intentions. The aim of this article is to evaluate the Country Personality Scale and to adapt it to the Portuguese context, proposing a model anchored in a reduced Country Personality Scale. Pretest (a sample of 115 Brazilians) and main survey data (685 responses from São Paulo and Bahia states in Brazil) are considered. Portugal is the stimulus country. The proposed research model relating the country's personality dimensions to its behavioral intentions to visit is estimated using structural equation modeling with AMOS, and the research hypotheses are tested. The results suggest that five dimensions (agreeableness, assiduousness, conformity, snobbism, and unobtrusiveness) should be considered when measuring country personality. There is a perception that this scale is a useful instrument for a quantitative approach to measuring a country personality construct and its impact on behavioral intentions, which can help researchers and marketers address international and cross-cultural marketing issues. Based on the main survey data, subjected to the personality trait frequency analysis, Portugal is classified as a conformist country.